Streptococcus pneumoniae colonisation in children and adolescents with asthma: impact of the heptavalent pneumococcal conjugate vaccine and evaluation of potential effect of thirteen-valent pneumococcal conjugate vaccine. Issue 1 (December 2015) - Esposito, Susanna; Terranova, Leonardo; Patria, Maria; Marseglia, Gian; Miraglia del Giudice, Michele; Bodini, Alessandro; Martelli, Alberto; Baraldi, Eugenio; Mazzina, Oscar; Tagliabue, Claudia; Licari, Amelia; Ierardi, Valentina; et al.
Abstract Background The main aim of this study was to evaluateStreptococcus pneumoniae carriage in a group of school-aged children and adolescents with asthma because these results might indicate the theoretical risk of invasive pneumococcal disease (IPD) of such patients and the potential protective efficacy of the 13-valent pneumococcal conjugate vaccine (PCV13). Methods Oropharyngeal samples were obtained from 423 children with documented asthma (300 males, 70.9 %), and tested for the autolysin-A-encoding (lytA ) and thewzg (cpsA ) gene ofS. pneumoniae by means of real-time polymerase chain reaction. Results S. pneumoniae was identified in the swabs of 192 subjects (45.4 %): 48.4 % of whom were aged <10 years, 46.9 % aged 10–14 years, and 4.7 % aged ≥15 years (p < 0.001). Carriage was significantly less frequent among the children who had received recent antibiotic therapy (odds ratio [OR 0.41]; 95 % confidence interval [95 % CI] 0.22–0.76). Multivariate analyses showed no association between carriage and vaccination status, with ORs of 1.05 (95 % CI 0.70–1.58) for carriers of any pneumococcal serotype, 1.08 (95 % CI 0.72–1.62) for carriers of any of the serotypes included in 7-valent pneumococcal conjugate vaccine (PCV7), and 0.76 (95 % CI 0.45–1.28) for carriers of any of the six additional serotypes of PCV13. Serotypes 19 F, 4 and 9 V were the most frequently identified serotypes in vaccinated subjects. Conclusions These results showed that carriage ofS. pneumoniae is relatively common in all school-aged children and adolescents with asthma, regardless of the severity of disease and the administration of PCV7 in the first years of life. This highlights the problem of the duration of the protection against colonisation provided by pneumococcal conjugate vaccine, and the importance of re-colonization by the same pneumococcal serotypes included in the previously used vaccine.